2010
DOI: 10.1038/onc.2010.455
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the physiological role of carbonic anhydrase IX in tumour pH regulation

Abstract: In this review, we discuss the role of the tumour-associated carbonic anhydrase isoform IX (CAIX) in the context of pH regulation. We summarise recent experimental findings on the effect of CAIX on cell growth and survival, and present a diffusion-reaction model to help in the assessment of CAIX function under physiological conditions. CAIX emerges as an important facilitator of acid diffusion and acid transport, helping to overcome large cell-to-capillary distances that are characteristic of solid tumours. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
190
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(194 citation statements)
references
References 85 publications
3
190
0
1
Order By: Relevance
“…The enhanced activity of CAs is often related to various diseases. The isoforms CA IX and CA XII were intensively investigated enzymes during the last decade due to their overexpression in various human cancers [5][6][7][8][9] . Much work has been done to design selective CA IX and CA XII inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced activity of CAs is often related to various diseases. The isoforms CA IX and CA XII were intensively investigated enzymes during the last decade due to their overexpression in various human cancers [5][6][7][8][9] . Much work has been done to design selective CA IX and CA XII inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Carbonic anhydrase (CA) enzymes catalyze the reversible reaction between carbon dioxide and bicarbonate: CO 2 + H 2 O ↔ HCO 3 -+ H + , and facilitate the transport of CO 2 and H + ions for pH regulation (Swietach et al, 2010). There are 15 CA isoforms, I to XV, in mammalian cells, located in the cytosol, mitochondrion, extracellular plasma membrane, or secreted.…”
Section: Molecular Targeting Of Acidosis-related Pathwaysmentioning
confidence: 99%
“…There are 15 CA isoforms, I to XV, in mammalian cells, located in the cytosol, mitochondrion, extracellular plasma membrane, or secreted. In particular, the isoform IX (CAIX) has been extensively studied in cancer biology (Swietach et al, 2010). The expression of CAIX is strongly induced by hypoxia and regulated by HIF-1.…”
Section: Molecular Targeting Of Acidosis-related Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…of !Our irradiation data for the multi-layer stacks showed that the sensitivity of cells to ionizing radiation decreased with increasing distance from the source of the oxygenated medium. To verify the cells were experiencing different oxygen tensions, we measured the expression of two markers for hypoxia in each of the six layers of the multilayer 3D culture: (i) hydroxy-HIF-1α, the predominant form of HIF-1α in cells when oxygenated (upon de-stacking) [68], and (ii) carbonic anhydrase 9 (CAIX), a HIF-1 inducible protein [69][70][71]. We stacked six sheets of lens paper-PVC composite containing overnight cultures of A549 (seeded at 2,000 A549 cells/zone) in an acrylic holder, cultured the stack for 4 days, disassembled the stacks into separate layers, and analyzed lysates for expression of hydroxy-HIF-1α and CAIX.…”
Section: Source Of Oxygenated Mediamentioning
confidence: 99%